Effects of hypertension on cancer survival: A meta‐analysis. (1st February 2021) - Petrelli, Fausto; Ghidini, Antonio; Cabiddu, Mary; Perego, Gianluca; Lonati, Veronica; Ghidini, Michele; Oggionni, Emanuela; Galli, Emilio; Moleri, Giovanna; Barni, Sandro; Bossi, Antonio Carlo; Colombelli, Paolo Luigi; et al.
Abstract: Background: Hypertension is usually associated with increased cardiovascular mortality. Uncertainty exists about the possible role of hypertension as a poor prognostic factor for cancer‐specific mortality (CSM). To assess the association between pre‐existing hypertension and the risk of mortality and relapse after a diagnosis of cancer, we performed a systematic review and meta‐analysis of published studies. Methods: PubMed, Scopus, Web of Science, the Cochrane Library and EMBASE were searched from inception until May 2020, without language restrictions, for observational studies reporting the prognosis of patients with hypertension and cancer. The primary outcome of the study refers to CSM in hypertensive vs nonhypertensive patients, and secondary endpoints were overall mortality (OM) and progression‐ or relapse‐free survival. The effect size was reported as hazard ratios (HRs) with 95% CIs. Results: Mortality and relapse associated with hypertension in patients with various cancers were evaluated among 1 603 437 participants (n = 66 studies). Overall, diagnosis of cancer and hypertension was associated with an increased independent risk of OM (HR = 1.2 [95% CI, 1.13‐1.27], P  < .01) and CSM (HR = 1.12 [95% CI, 1.04‐1.21], P  < .01) but not of relapse (HR = 1.08 [95% CI, 0.98‐1.19], P  = .14). Conclusions: Among cancer patients, those with pre‐existing hypertension have a poorer outcome, probably due to multifactorial reasons. Adequate control of lifestyle, more intensive follow‐ups, monitoring for hypertension‐ and anticancer‐related cardiovascular complications, and establishing multidisciplinary cardio‐oncology units can be useful measures for reducing mortality and improving care in this setting.